IDENTIFICATION MICROPLASTIC WASTE IN SEAWATER AND THE DIGESTIVE ORGANS OF SENANGIN FISH (E. tetradactylum) AT DUMAI CITY SEA WATERS - Mirad, Awis; Yoswaty, Dessy; Thamrin, Thamrin (Asian Journal of Aquatic Sciences, 2020)
The research was conducted on November 2019 with sampling at the sea waters of Dumai, Riau province. Further, analysis samples in the Marine Chemistry’s Laboratory on Marine Sciences Department in Fisheries and Marine Faculty University of Riau. Method used method of survey. The form of data collection is the primary data obtained from survey activities and observation data from samples that have been analyzed in the laboratory. The results of the study showed that the type of microplastic found in sea water and Senangin (E. Tetradactylum) is a type of microplastic fiber, fragments, and film. Microplastic pellet type was not finding in this research. The abundance of microplastics in seawater samples ranges from 333,3333-456,6667 particles/m3, while the abundance of microplastics in Senangin fish (E. tetradactylum) is 966,6667-1933,3333 particles/Ind.